GOVERNANCE ANALYSIS OF THE IMPLEMENTATION OF THE FREE NUTRITIOUS MEAL PROGRAM - Santoso, Ary; Melianawati , Briliantina Dwi; Ayuningtyas , Eka Avianti (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
The Free Nutritious Meal Program (MBG) is one of the government’s strategic initiatives aimed at improving nutritional quality and public welfare, particularly for school-aged children. This article seeks to identify key governance factors of the MBG program that influence its implementation effectiveness and to provide policy recommendations to strengthen the governance of the National Nutrition Agency (BGN). This study employs a combination of approaches and methodologies, including the Triangulation Model, Analytical Hierarchy Process (AHP), and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. The triangulation model identified eight (8) priority governance criteria for the MBG program: Participatory, Transparency, Accountability, Effectiveness-Efficiency, Collaboration, Digital Technology, Decentralization, and Program Evaluation. AHP results indicate that Effectiveness and Efficiency are the primary success factors of the MBG program, while Digital Technology serves as an enabler of Transparency and Evaluation, with improvements in Participation and Collaboration driven by a multi-stakeholder approach.